Monitoring the impact of desert dust outbreaks for air quality for health studies. (September 2019) - Querol, X.; Tobías, A.; Pérez, N.; Karanasiou, A.; Amato, F.; Stafoggia, M.; Pérez García-Pando, C.; Ginoux, P.; Forastiere, F.; Gumy, S.; Mudu, P.; Alastuey, A.
Abstract: We review the major features of desert dust outbreaks that are relevant to the assessment of dust impacts upon human health. Our ultimate goal is to provide scientific guidance for the acquisition of relevant population exposure information for epidemiological studies tackling the short and long term health effects of desert dust. We first describe the source regions and the typical levels of dust particles in regions close and far away from the source areas, along with their size, composition, and bio-aerosol load. We then describe the processes by which dust may become mixed with anthropogenic particulate matter (PM) and/or alter its load in receptor areas. Short term health effects are found during desert dust episodes in different regions of the world, but in a number of cases the results differ when it comes to associate the effects to the bulk PM, the desert dust-PM, or non-desert dust-PM. These differences are likely due to the different monitoring strategies applied in the epidemiological studies, and to the differences on atmospheric and emission (natural and anthropogenic) patterns of desert dust around the world. We finally propose methods to allow the discrimination of health effects by PM fraction during dust outbreaks, and a strategy to implement desert dust alert and monitoring systems for health studies and air quality management. Graphical abstract: Unlabelled Image Highlights: We discuss on exposure relevant dust and meteorological patterns relevant to epidemiological studies. We suggest evaluating health effects for mineral dust and anthropogenic PM during the episodes, as well as bulk PM. Short term health effects of desert dust in different world regions might be differently associated with these PM types. A harmonized way of evaluating these health effects is needed to compare results from different regions. A strategy to monitor these PM components and to implement desert dust alert systems for health studies is presented.